Upaya Penurunan Intensitas Halusinasi Dengan Cara Mengontrol Halusinasi Di Rsjd Arif Zainudin Surakarta - Widuri, Ninik Retna, Arif Widodo, A. Kep., M.Kes (2016)
Background: it is estimated that over 90% of clients with schizophrenia experience hallucinations. Hallucination is the loss of human ability to distinguish internal stimuli (thoughts) and external stimuli (the outside world) so that the client member perception or opinion about the object or the environment without any real stimulus. Hallucination experienced by clients species vary, but most clients schizophrenia have auditory hallucinations. Auditory hallucinations can be controlled in four ways, namely rebuke hallucinations, taking medication regularly, conversing with others, perform activities scheduled. Objective: The author can understand nursing care in patients with a diagnosis of sensory perception disorders: hallucinations ward Abimanyu RSJD dr. Arif Zainudin Surakarta. Methods: The method used was descriptive, while the sample was Mr. B, this data is obtained by means of interviews ranging from assessment has been done, planned actions that will be given to clients, do the plans that have been made, and to evaluate action taken. Result: After 3 days of nursing care for patients with impaired sensory perception: hallucinations auditory hallucinations experienced to know and be able to control and reduce the intensity of auditory hallucinations by controlling hallucinations. The issue is resolved in part. Conclusion: Nursing problems resolved partially, thus requiring further treatment and cooperation with other medical teams, cliens and families that are indispensable for the success of nursing care. There was a decrease in the intensity of hallucinations before and after the intervention.